An update on thymectomy in myasthenia gravis. (2nd September 2019) - Evoli, Amelia; Meacci, Elisa
ABSTRACT: Introduction : Myasthenia gravis (MG) is one of the best treatable autoimmune diseases. However, in most patients, treatment is necessarily long-term and related side effects are a serious burden. Thymectomy has a special place in the disease management as a non-pharmacological disease-modifying therapy. For several decades, its role has only been supported by observational studies. Despite the recently achieved class I evidence, many questions remain unaddressed. Areas covered : This review discusses the pathogenic role of the thymus and evidence and controversies concerning therapeutic thymectomy. It also describes minimally invasive techniques that have largely replaced open surgery and the available evidence in MG patients. Expert opinion : Thymectomy plays a primary role in MG management, though its use is still controversial in some disease subtypes. Patient selection for surgery and adequate pre-operative MG control are critical. Thymectomy must ensure the exeresis of the whole thymus together with peri-thymic fat tissue. Minimally invasive techniques have many advantages over open approaches, provided they are as extensive as trans-sternal thymectomy. The investigation of thymectomy-related biomarkers will contribute to enhance the knowledge of its impact on the specific immune response.